Autoimmune cholestatische Lebererkrankungen - Mayer, Lena Sophie; Käser, Rafael; Böttler, Tobias (DMW - Deutsche Medizinische Wochenschrift, 2020)
Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are rare, autoimmune mediated cholestatic liver diseases. Other auto-immune diseases are often associated with PBC and PSC, and inflammatory bowel disease is present in the majority of PSC patients. In the course of disease, chronic inflammation in the liver leads to fibrotic restructuring and ultimately cirrhosis. The diagnosis of PBC is confirmed serologically and PSC is diagnosed via cholangiography, whereas MRCP is preferred over ERCP. For PBC, the first line therapy is ursodeoxycholic acid (UDCA). Prognosis is strongly dependent on the response to UDCA. The only approved second line therapy is obeticholic acid (OCA). Alternatively, Budesonide or Fibrates are often used off-label. In the management of PSC, prevention and adequate treatment of bacterial cholangitis play a major role. For both PBC and PSC novel treatments are currently being tested in clinical trials. Disease management should address compromising symptoms like pruritus and sicca as well as complications due to maldigestion and concomitant autoimmune diseases. The only curative treatment available is liver transplantation and should be considered at a MELD score of 15.
Keywords: primär biliäre Cholangitis; primär sklerosierende Cholangitis; Cholestase; Ursodesoxycholsäure; Obeticholsäure